Pengembangan Sistem Informasi Transaksi Penjualan Dan Pembelian Pada Udmandiri Berbasis Web Menggunakan Metode Usecase Driven - M. Imam Yahya; M Najamuddin Dwi Miharja (DPPM Universitas Pelita Bangsa, 2022)
This final project describes the sales and purchase transactions at UD Mandiri Using the Waterfall method and Usecase Driven as a method of developing the system with the PHP 7 programming language, Usecase, ERD and data normalization which contains an explanation of how to analyze the data and information obtained, the current system is still using a manual work system so that a lot of data is not updated, resulting in inventory often running out without realizing it, from the results of observations and information obtained from the UDMandiri business owner, the author applies it in digital form or computer automation, where all activities buying and selling transactions are carried out automatically, making it more effective and efficient. Keywords: Sales system, Use case driven, UML, Web, PHP